Mapuche Transitions from Education to Work: Vulnerable Transitions and Unequal Outcomes. Issue 2 (June 2022) - Castillo, Javier; Webb, Andrew; Biehl, Andrés
This article investigates vulnerabilities in transitions from secondary and tertiary education to work among the indigenous Mapuche youth in Chile. The study draws from a 2014 social survey and qualitative in-depth interviews of indigenous students in secondary and higher education focused on the magnitude of accumulative disadvantages and the decision processes involved in their choice of future life-paths. Despite socioeconomic convergence with the non-Mapuche population, the results reveal the importance of urban economic conditions and previous educational disadvantages in shaping the aspirations of Mapuche youth.